Seismic Behavior of Colliding Buildings, Incorporating Soil-structure Interaction and Accounting for Variability in Structural Parameters, Soil Parameters, and Seismic Action - Asmouni, Ikhlasse Kheira; Mekki, Mohammed; Bensafi, Mohammed (Periodica Polytechnica Civil Engineering, 2024)
Pounding between buildings that are not sufficiently separated has been observed several times during earthquakes. This destructive impact may severely damage the structure and lead to its collapse. Although it is impossible to completely eliminate such losses, measures can be taken to minimize them. This article investigates the effect of the variability of structural parameters, soil parameters, and seismic action on the seismic response of two colliding buildings, taking the soil-structure interaction (SSI) into account. Two adjacent structures closely separated, modeled as inelastic lumped mass systems with different structural characteristics, were considered in this study. Both structures were modeled in the analysis using multi-degree-of-freedom (MDOF) systems, and the pounding was simulated using the modified linear viscoelastic model. The analysis was conducted in two cases: probabilistic analysis and deterministic analysis. Probability curves were established to analyze the effect of the variability of the parameters on the responses of the two colliding buildings. The comparison between the two analyses indicates that the probabilistic analysis is more precise than the deterministic analysis. It has been indicated that taking into account the variability of structural parameters, soil parameters, and seismic action is efficient in determining the realistic behavior of colliding buildings. Additionally, pounding is more critical in the case of buildings founded on very soft soil, followed by those on soft soil, then on hard soil, and finally on rocky soil.